Seawater carbonate chemistry and oxygen consumption rates and ammonia excretion rates of Mactra veneriformis - Limei Chen; Gengyin Huang; Shuang Liang; Jian Liang; Hefeng Wang; Huiru Liu; Xiaoyu Wang; Li Li; Yongjun Guo; Wenguang Liu (PANGAEA, 2024)
In this study, oxygen consumption rate, ammonia excretion rate, and transcriptome sequencing of mantle tissue analyses were conducted in white and purple shell-color populations of M. veneriformis under OA stress (pH = 7.6). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2024-12-17.